Breaking connections in the representations of "I - Stranger" interaction: Determinants and prerequisites (the case study of extremist groups) - Elena V. Ryaguzov (Saratov State University, 2021)
The article presents the results of a theoretical reflection on the main prerequisites and determinants of extremism as a complex sociopsychological phenomenon which poses a serious threat to international security. Purpose: to study social and socio-psychological determinants which contribute to and lead to breaking connections in the "I - Stranger" dyad as fundamentals of sociability (on the example of extremist groups). We identified social and socio-psychological factors (social tension, instability, uncertainty, stratified social isolation, group status, perceived discrimination, group ideology), serving as prerequisites for extremism, which contribute to breaking ties in the "I - Stranger" dyad along with psychological predictors. The example of extremist groups has shown that, on the one hand, breaking these connections leads to an exaggerated sense of "We", erosion of individuality, depreciation of one's own life and "self-erasure" against the background of group superiority and narcissism, on the other hand, it leads to depersonalization, demonization and dehumanization of "Stranger", positioning him / her as a person who is not fully human, a faceless enemy. It has been established that breaking connections in representations of "I - Stranger" interaction facilitates the process associated with losing a sense of self as a key point in the construction and cognition of the social world and its replacement by the collective "We". The applied aspect of the problem under study is the possibility of using the results of the analysis for developing preventive socio-psychological programmers and trainings aimed at preventing extremism and religious radicalism in the young people's environment.